Konsep landasan filosofis pengembangan ilmu bersumber pada nilai-nilai ke-ugm-an - Heri Santoso; Koento Wibisono Siswomihardjo,; Arqom Kuswanjono (Jurnal Kawistara, 2017)
This research is motivated by crisis, especially of UGM (Universitas Gadjah Mada) identity and of philosophical foundations of its scientific development. This study aims to inventory, analyzesynthesize, critically evaluate, as well as construct a philosophical foundation of scientific development originating in UGM values. The study employs a reflective, systematic philosophical research model.